Developing Green Banking Performance Measurement for Islamic Bank with Maqasid Shariah - Jannah, Siti Nur; Surbakti, Muhammad Syarif; Ascarya, Ascarya (Universitas Mercu Buana, 2025)
The application of green banking (GB) practices can be a solution to various environmental problems and help achieve the SDGs. However, the performance of GB implementation in Indonesia’s Islamic Bank is still unclear due to the unavailability of instruments to measure its implementation. Even though information regarding GB implementation in Indonesia’s Islamic bank is urgently needed to achieve the SDGs and sharia goals or maqasid sharia. This study aims to develop index for measuring GB performance in Islamic Bank using maqasid syariah and ESG as framework, namely green banking maqasid index or GBMI. Model development and weighting in this study use the Delphi-ANP (Analytic Network Process) method. The results of this study reveal the order of priority and weight of variables related to GBMI measurement. There are 6 main priorities out of 18 important variables in ESG and their weights, namely green human resource management (HRM) (0.075), health and safety of the workplace (0.072), green product and service (0.070), green strategic planning (0.069), and elimination of wastage (0.065). These results also indicate that green HRM is among the most emphasized variables in the application of GB concept. Thus, educating HRM to understand the GB concept well is quite important in the initial stage of implementing GB practices in Islamic banks.